The Effect of Various Components of Triglycerides and Conversion Factor on Energy Consumption in Biodiesel Production - Sariah, Abang; S. M., Anisuzzaman; Awang, Bono; D., Krishnaiah; Afikah, N.A. (Walter de Gruyter GmbH, 2017)
Major components of triglycerides in palm oil are palmitic acid, oleic acid, and linoleic acid, in which the presence of these components effects the final purity of a biodiesel. Since reaction process and type of catalyst influence the composition of the free fatty acid (FFA) ASPEN HYSYS was used to simulate a biodiesel production process. Furthermore, higher yield of biodiesel was desired to increase its efficiency as fuel application. Palm oil was taken as the raw material at different components of FFA wt by using sulphated zirconium (SZ) as the catalyst. Three simulations of biodiesel production processes were performed using ASPEN HYSYS based on 99 of conversion factor to determine the energy consumption and the results were compared. The conversion factor for each component and the mixture of all of the components was discussed. Results showed that triolein with 0.12 wt of oleic acid produced 99.75 of biodiesel, while tripalmitin with 0.5 wt of palmitic acid is the most abundant FFA in palm oil producing 99.67 of biodiesel. The total energy consumption in the three processes were different because, different types of feedstocks and unit operations arrangements have been used. Â© 2017 Walter de Gruyter GmbH, Berlin/Boston 2017.